An entropy-controlled textured BaBi4Ti4O 15 Dielectric energy storage thin films and their preparation methods
Patent Information
- Application Number
- CN202611217945.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-12
- Publication Date
- 2026-11-03
AI Technical Summary
In existing BaBi4Ti4O15-based dielectric materials, polarization intensity and breakdown intensity have an inverted coupling relationship, making it difficult to achieve high polarization intensity and high breakdown intensity simultaneously in the same crystal axis direction, thus limiting the improvement of energy density.
By employing a texturing strategy to grow thin films along the c-axis orientation, and combining this with a configuration entropy strategy, the polarization intensity is enhanced while maintaining the layered structure characteristics. By utilizing the high breakdown characteristics of BaBi4Ti4O15-based materials along the c-axis direction, the inverted coupling relationship between polarization intensity and breakdown intensity is broken.
It achieves a threefold increase in breakdown strength, a simultaneous increase in polarization strength, and a 9-14 times increase in energy density. It also features excellent frequency, temperature, and cycling stability, and its simple fabrication method makes it suitable for large-area applications.
Smart Images

Figure CN123035686A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of dielectric energy storage materials technology, specifically relating to an entropy-controlled textured BaBi4Ti4O 15 Dielectric energy storage thin films and their preparation methods. Background Technology
[0002] Dielectric film capacitors, with their advantages of ultrafast charge / discharge rates, ultra-high power density, high withstand voltage, and long cycle life, hold significant application potential in fields such as new energy vehicles, high-voltage direct current transmission, and pulsed power systems. However, the energy density of dielectric materials is determined by both polarization intensity and breakdown field strength, and there is an inherent inverse coupling relationship between the two: increasing polarization intensity often leads to local electric field distortion and weakening of polar bonds, thereby reducing breakdown resistance. This contradiction severely restricts further improvements in energy storage density. In particular, achieving an energy density exceeding 150 J / cm³ under conditions of energy storage efficiency higher than 90% has become a key bottleneck that urgently needs to be overcome in the current field of dielectric energy storage.
[0003] Currently, simple perovskite-based dielectric materials are the main focus of research. Their polarization intensity and breakdown field strength are highly dependent on the single perovskite unit. The strong polarization caused by the relative displacement of anions and cations also causes local electric field distortion, weakens the chemical bond strength, and is prone to inducing breakdown. Therefore, it is difficult for this type of material to obtain both high polarizability and high withstand voltage characteristics at the same time.
[0004] BaBi4Ti4O 15 The base material belongs to the Aurivillius phase of layered perovskites, consisting of alternating perovskite-like layers and fluorite-like layers stacked along the c-axis to form a natural superlattice. In this type of material, the polarization of the perovskite-like layers is confined within the ab plane, while the high breakdown characteristics are oriented along the c-axis. This crystallographic anisotropy has led to current research focusing primarily on polycrystalline systems, making it difficult to simultaneously achieve high polarization and high resistivity along the same crystal axis. The inverted coupling relationship between polarization and breakdown remains unresolved.
[0005] Therefore, a BaBi4Ti4O material capable of breaking the aforementioned inverted coupling relationship and simultaneously achieving high polarization intensity and high breakdown strength in the same crystal axis direction is provided. 15 The development of dielectric materials remains a technological challenge in this field. Summary of the Invention
[0006] One of the objectives of this invention is to address the shortcomings of existing BaBi4Ti4O 15 The inverse coupling between polarization intensity and breakdown strength in basic dielectric energy storage materials poses a technical problem that hinders further improvements in energy density. This paper proposes an entropy-controlled textured BaBi4Ti4O... 15A method for preparing a base dielectric energy storage thin film. A texturing strategy is used to grow the film along the c-axis orientation, utilizing BaBi4Ti4O. 15 The base material exhibits crystallographic anisotropy with high breakdown characteristics along the c-axis to improve breakdown strength. Simultaneously, through a configuration entropy strategy, the polarization intensity is enhanced while maintaining the layered structure characteristics, thereby simultaneously achieving high polarization intensity and high resistivity in the same crystal axis direction. This breaks the inverted coupling relationship between polarization intensity and breakdown strength, achieving a synergistic improvement of both.
[0007] To achieve the above objectives, the present invention adopts the following technical solution: an entropy-controlled textured BaBi4Ti4O 15 The method for preparing a dielectric energy storage thin film includes the following steps: S1. Preparation of precursor solution: Weigh out barium, bismuth, titanium, hafnium, zirconium, tin, and manganese sources according to the molar ratio of metal elements 1:4.2:(3.95-3x):x:x:x:0.05, where 0≤x≤0.3; dissolve each metal source in a solvent to obtain a mixed solution, wherein the molar concentration of the main matrix metal barium (Ba) in the mixed solution is 0.1 mol / L; after heating and stirring, stirring at room temperature, and aging by static aging, obtain BaBi4Ti4O. 15 Precursor solution; S2. Plasma pretreatment is performed on the surface of the (001) oriented perovskite single crystal substrate to obtain an activated surface; a conductive oxide electrode precursor solution is coated on the activated surface, followed by low-temperature heating and drying, medium-temperature pyrolysis to remove organic components and high-temperature annealing and crystallization treatment, and the steps of coating to high-temperature annealing and crystallization treatment are repeated at least once to form a bottom electrode layer. S3. Coat the bottom electrode layer with the BaBi4Ti4O prepared in step S1. 15 The precursor solution was then subjected to a series of treatments, including low-temperature drying, medium-temperature pyrolysis to remove organic components, and high-temperature annealing crystallization, to produce BaBi4Ti4O. 15 The dielectric energy storage film is grown along the c-axis orientation and the process of high-temperature annealing and crystallization is repeated at least once to form an entropy-controlled textured BaBi4Ti4O. 15 Dielectric energy storage thin films; Steps S1 and S2 are not in any particular order.
[0008] As one of the entropy-regulating textures, BaBi4Ti4O 15 The preparation method of the dielectric energy storage thin film has been further improved: Preferably, in step S1, x is 0.1, and the barium source, bismuth source, titanium source, hafnium source, zirconium source, tin source and manganese source are weighed according to the molar ratio of metal elements 1:4.2:3.65:0.1:0.1:0.1:0.05.
[0009] Preferably, the barium source in step S1 is barium acetate, the bismuth source is bismuth acetate, the titanium source is tetrabutyl titanate, the hafnium source is hafnium acetylacetonate, the zirconium source is zirconium n-propoxide, the tin source is tin isooctanoate, the manganese source is manganese acetate tetrahydrate, and the solvent is propionic acid.
[0010] Preferably, in step S1, the heating and stirring temperature is 70-90 ℃, the stirring time is 10-20 min, the room temperature stirring time is 6-7 h, and the aging time is 3-90 days.
[0011] Preferably, in step S2, the conductive oxide electrode precursor solution is coated and heat-treated to form La. 0.7 Sr 0.3 MnO3 or LaNiO3 conductive oxide electrode films.
[0012] Preferably, in step S2, the conductive oxide electrode precursor solution contains substances similar to the target compound La. 0.7 Sr 0.3 The corresponding molar ratio of MnO3 to lanthanum salt, strontium salt, manganese salt, and solvent, wherein the lanthanum salt is lanthanum nitrate with a concentration of 0.07-0.21 mol / L; the strontium salt is strontium acetate with a concentration of 0.03-0.09 mol / L; the manganese salt is manganese acetate tetrahydrate with a concentration of 0.1-0.3 mol / L; and the solvent is one or more of acetic acid, deionized water, and ethylene glycol methyl ether. Alternatively, the conductive oxide electrode precursor solution contains a lanthanum salt, a nickel salt, and a solvent in a molar ratio corresponding to the target LaNiO3, wherein the lanthanum salt is lanthanum nitrate with a concentration of 0.1-0.3 mol / L, the nickel salt is nickel acetate tetrahydrate with a concentration of 0.1-0.3 mol / L, and the solvent is ethylene glycol methyl ether.
[0013] Preferably, in step S2, the perovskite single crystal substrate is a LaAlO3 single crystal substrate or a SrTiO3 single crystal substrate; plasma pretreatment is performed in an air atmosphere with a processing power of 7-18 W, a processing time of 5-15 min, and a working pressure of 30-60 Pa.
[0014] Preferably, the coating method in step S2 is spin coating, with a spin coating speed of 3000-5000 r / min and a time of 20-30 s; low-temperature heating drying at 120-200 ℃ for 1-2 min; medium-temperature pyrolysis at 350-450 ℃ for 5-20 min; and high-temperature annealing crystallization treatment at 700-900 ℃ for 20-30 min, repeated 2-8 times.
[0015] Preferably, the coating method described in step S3 is spin coating, with a spin coating speed of 3000-6000 r / min and a time of 20-30 s; low-temperature heating drying at a temperature of 120-200 ℃ and a time of 1-2 min; medium-temperature pyrolysis at a temperature of 350-450 ℃ and a time of 5-20 min; and high-temperature annealing crystallization treatment at a temperature of 600-750 ℃ and a time of 20-30 min, repeated 10-18 times.
[0016] A second objective of this invention is to provide a textured BaBi4Ti4O with entropy control as described in any one of the above claims. 15 Entropy-modulated textured BaBi4Ti4O prepared by a method for preparing dielectric energy storage thin films. 15 Dielectric energy storage film.
[0017] The beneficial effects of this invention are as follows: (1) This invention uses a texturing strategy to grow thin films oriented along the c-axis, utilizing BaBi4Ti4O 15 The base material exhibits crystallographic anisotropy with high breakdown characteristics along the c-axis, effectively improving the breakdown strength. Simultaneously, a configurational entropy strategy enhances the polarization intensity, decoupling the inverse coupling between polarization intensity and breakdown strength, achieving a synergistic improvement in both. The prepared entropy-controlled textured film demonstrates a breakdown strength more than three times higher than that of polycrystalline materials of the same composition, while maintaining comparable polarization intensity under the same electric field, and exhibiting a 9-14 times higher energy density. Within the range of 0 ≤ x ≤ 0.2, the breakdown strength gradually increases, reaching a high of 5.33 MV / cm at x = 0.2. Within the range of 0 ≤ x ≤ 0.1, the polarization intensity increases synchronously, achieving 181.3 J / cm at x = 0.1. 3 It has an energy density and a storage efficiency of 91.2%.
[0018] (2) The entropy-controlled textured BaBi4Ti4O prepared in this invention 15 The dielectric energy storage film exhibits excellent frequency stability, temperature stability, and cycle stability: energy density and energy storage efficiency remain essentially unchanged within the frequency range of 0.5–50 kHz; energy density and energy storage efficiency show minimal changes within the temperature range of 173–573 K for the products of Examples 2 and 3; and the products of Examples 2 and 3 show relatively stable energy density and energy storage efficiency within a 10°C range. 7 The energy density and energy storage efficiency remain almost unchanged throughout the charge-discharge cycle, demonstrating superior energy storage performance and cycle stability.
[0019] (3) The preparation method provided by the present invention is simple and time-saving, which is conducive to large-area preparation and has broad application prospects in the field of dielectric energy storage. Attached Figure Description
[0020] Figure 1 The entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 XRD pattern of the dielectric energy storage thin film.
[0021] Figure 2 The entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 SEM image of the dielectric energy storage film, scale bar 500 nm.
[0022] Figure 3 The entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 BaBi4Ti4O4 dielectric energy storage thin film and BaBi4Ti4O4 prepared in Comparative Example 1 15 Breakdown strength curve of the base film (corresponding to E) b The curves, and the polarization intensity curves of the films prepared in Examples 1-4 under an electric field of 2.5 MV / cm (corresponding to P) m curve).
[0023] Figure 4 The figures are hysteresis loop diagrams of the films prepared in Examples 1 to 4 under electric fields ranging from -6 MV / cm to 6 MV / cm, where (a), (b), (c), and (d) are hysteresis loop diagrams of Examples 1, 2, 3, and 4, respectively.
[0024] Figure 5 The graph shows the changes in energy density and energy storage efficiency of the thin films prepared in Examples 1-4 as a function of electric field strength.
[0025] Figure 6 The graph shows the energy density and energy storage efficiency of the thin films prepared in Examples 1-4 as a function of frequency under an electric field of 2 MV / cm.
[0026] Figure 7 The graph shows the changes in energy density and energy storage efficiency of the thin films prepared in Examples 1-4 under an electric field of 2 MV / cm as a function of temperature.
[0027] Figure 8 The graph shows the changes in energy density and energy storage efficiency of the thin films prepared in Examples 1-4 under an electric field of 2 MV / cm as a function of the number of charge-discharge cycles.
[0028] Figure 9 BaBi4Ti4O prepared for Comparative Example 1 15 Hysteresis loop diagram of the base film under electric fields ranging from -1.5 MV / cm to 1.5 MV / cm. Detailed Implementation
[0029] This invention provides an entropy-controlled textured BaBi4Ti4O 15This invention relates to a dielectric energy storage thin film and its preparation method. To make the objectives, technical solutions, and effects of this invention clearer and more explicit, the following provides a more detailed description. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of the invention.
[0030] Example 1
[0031] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1. 0.1277 g barium acetate (99.99% purity), 0.8109 g bismuth acetate (99.999% purity), 0.6858 g tetrabutyl titanate (98% purity), and 0.0062 g manganese acetate tetrahydrate (99% purity) were dissolved in 5 mL of propionic acid to obtain a mixed solution. The molar concentration of the matrix metal (barium site Ba) in the mixed solution was controlled at 0.1 mol / L, with the molar ratio of barium, bismuth, titanium, and manganese being 1:4.2:3.95:0.05. To compensate for the volatilization of bismuth during heat treatment, bismuth was added in excess by 5%. The solution was heated and stirred at 90 °C for 10 min to completely dissolve it. Then, it was cooled to room temperature and continuously stirred for 6.5 h to ensure thorough and uniform mixing. The resulting precursor solution was allowed to stand and age for 3 days to obtain BaBi4Ti4O. 15 Precursor solution.
[0032] S2. Dissolve 0.6068 g of lanthanum nitrate (99.9% purity), 0.1315 g of strontium acetate (98% purity), and 0.4951 g of manganese acetate tetrahydrate (99% purity) in a mixed solution of 5 mL acetic acid, 1 mL deionized water, and 5 mL ethylene glycol methyl ether. Heat and stir at 90°C for 20 min to ensure complete dissolution. Then, cool to room temperature and stir continuously for 7 h to ensure thorough mixing. Allow the solution to stand and age for 12 h to obtain the conductive oxide electrode La. 0.7 Sr 0.3 MnO3 precursor solution.
[0033] A (001) oriented LaAlO3 single crystal substrate was pretreated with plasma in air for 10 min at a power of 18 W and a working pressure of 60 Pa. A conductive oxide electrode, La, was then spin-coated onto the pretreated substrate. 0.7 Sr 0.3 The MnO3 precursor solution was spin-coated at 4000 r / min for 30 s. Then it was heated and dried at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter. Finally, it was annealed at 900 ℃ for 30 min to crystallize. The spin-coating, pyrolysis and annealing steps were repeated 4 times to obtain the bottom electrode layer.
[0034] S3. Spin-coat BaBi4Ti4O with an entropy value of 0.7 R onto the surface of the prepared bottom electrode layer. 15 The precursor solution was spin-coated at 6000 r / min for 20 s; then heated to 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally annealed at 600 ℃ for 30 min to crystallize. This spin-coating, pyrolysis, and annealing process was repeated 16 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95- 3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value 0.
[0035] Example 2
[0036] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1. Dissolve 0.1277 g barium acetate (99.99% purity), 0.8109 g bismuth acetate (99.999% purity), 0.6338 g tetrabutyl titanate (98% purity), 0.0296 g hafnium acetylacetonate (97% purity), 0.0234 g zirconium propoxide (70% purity), 0.0211 g tin isooctanoate (96% purity), and 0.0062 g manganese acetate tetrahydrate (99% purity) in 5 mL of propionic acid to obtain a mixed solution. Control the molar concentration of the matrix metal (barium site Ba) in the mixed solution to be 0.1 mol / L. The molar ratio of the metal elements barium, bismuth, titanium, hafnium, zirconium, tin, and manganese is 1:4.2:3.65:0.1:0.1:0.1:0.05. To compensate for the volatilization of bismuth during heat treatment, bismuth is added in excess by 5%. The solution is placed at 90°C. The solution was heated and stirred at ℃ for 10 min to completely dissolve the precursor, then cooled to room temperature and stirred continuously for 6.5 h to ensure thorough and homogeneous mixing. The resulting precursor solution was then allowed to stand and age for 3 days to obtain BaBi4Ti4O. 15 Precursor solution.
[0037] S2. Dissolve 0.6068 g of lanthanum nitrate (99.9% purity), 0.1315 g of strontium acetate (98% purity), and 0.4951 g of manganese acetate tetrahydrate (99% purity) in a mixed solution of 5 mL acetic acid, 1 mL deionized water, and 5 mL ethylene glycol methyl ether. Heat and stir at 90°C for 20 min to ensure complete dissolution. Then, cool to room temperature and stir continuously for 7 h to ensure thorough mixing. Finally, allow the solution to stand and age for 12 h to obtain the conductive oxide electrode La. 0.7 Sr 0.3 MnO3 precursor solution.
[0038] A (001) oriented LaAlO3 single crystal substrate was pretreated with plasma in air for 10 min at a power of 18 W and a working pressure of 60 Pa. A conductive oxide electrode, La, was then spin-coated onto the pretreated substrate. 0.7 Sr 0.3 The MnO3 precursor solution was spin-coated at 4000 r / min for 30 s. Then it was heated and dried at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter. Finally, it was annealed at 900 ℃ for 30 min to crystallize. The spin-coating, pyrolysis and annealing steps were repeated 4 times to obtain the bottom electrode layer.
[0039] S3. Spin-coat BaBi4Ti4O with an entropy value of 1.05 R onto the surface of the prepared bottom electrode layer. 15 The precursor solution was spin-coated at 6000 r / min for 20 s; then heated to 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally annealed at 625 ℃ for 30 min to crystallize. This spin-coating, pyrolysis, and annealing process was repeated 15 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95- 3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value of 0.1.
[0040] Example 3
[0041] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1. Dissolve 0.1277 g barium acetate (99.99% purity), 0.8109 g bismuth acetate (99.999% purity), 0.5817 g tetrabutyl titanate (98% purity), 0.0593 g hafnium acetylacetonate (97% purity), 0.0468 g zirconium propoxide (70% purity), 0.0422 g tin isooctanoate (96% purity), and 0.0062 g manganese acetate tetrahydrate (99% purity) in 5 mL of propionic acid to obtain a mixed solution. Control the molar concentration of the matrix metal (barium site Ba) in the mixed solution to be 0.1 mol / L. The molar ratio of the metal elements barium, bismuth, titanium, hafnium, zirconium, tin, and manganese is 1:4.2:3.35:0.2:0.2:0.2:0.05. To compensate for the volatilization of bismuth during heat treatment, bismuth is added in excess by 5%. The solution is placed at 90°C. The solution was heated and stirred at ℃ for 10 min to completely dissolve the precursor, then cooled to room temperature and stirred continuously for 6.5 h to ensure thorough and uniform mixing. The resulting precursor solution was then allowed to stand and age for 3 days to obtain BaBi4Ti4O. 15 Precursor solution.
[0042] S2. Dissolve 0.6068 g of lanthanum nitrate (99.9% purity), 0.1315 g of strontium acetate (98% purity), and 0.4951 g of manganese acetate tetrahydrate (99% purity) in a mixed solution of 5 mL acetic acid, 1 mL deionized water, and 5 mL ethylene glycol methyl ether. Heat and stir at 90°C for 20 min to ensure complete dissolution. Then, cool to room temperature and stir continuously for 7 h to ensure thorough mixing. Finally, allow the solution to stand and age for 12 h to obtain the conductive oxide electrode La. 0.7 Sr 0.3 MnO3 precursor solution.
[0043] A (001) oriented LaAlO3 single crystal substrate was pretreated with plasma in air for 10 min at a power of 18 W and a working pressure of 60 Pa. A conductive oxide electrode, La, was then spin-coated onto the pretreated substrate. 0.7 Sr 0.3 The MnO3 precursor solution was spin-coated at 4000 r / min for 30 s. Then it was heated and dried at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter. Finally, it was annealed at 900 ℃ for 30 min to crystallize. The spin-coating, pyrolysis and annealing steps were repeated 4 times to obtain the bottom electrode layer.
[0044] S3. Spin-coat BaBi4Ti4O with an entropy value of 1.29 R onto the surface of the prepared bottom electrode layer. 15The precursor solution was spin-coated at 6000 r / min for 20 s; then heated and dried at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally annealed at 650 ℃ for 30 min to crystallize. This spin-coating, pyrolysis, and annealing process was repeated 17 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95- 3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value of 0.2.
[0045] Example 4
[0046] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1. Dissolve 0.1277 g barium acetate (99.99% purity), 0.8109 g bismuth acetate (99.999% purity), 0.5296 g tetrabutyl titanate (98% purity), 0.0889 g hafnium acetylacetonate (97% purity), 0.0702 g zirconium propoxide (70% purity), 0.0633 g tin isooctanoate (96% purity), and 0.0062 g manganese acetate tetrahydrate (99% purity) in 5 mL of propionic acid to obtain a mixed solution. Control the molar concentration of the matrix metal (barium site Ba) in the mixed solution to be 0.1 mol / L. The molar ratio of the metal elements barium, bismuth, titanium, hafnium, zirconium, tin, and manganese is 1:4.2:3.05:0.3:0.3:0.3:0.05. To compensate for the volatilization of bismuth during heat treatment, bismuth is added in excess by 5%. The solution is placed at 90°C. The solution was heated and stirred at ℃ for 10 min to completely dissolve the precursor, then cooled to room temperature and stirred continuously for 6.5 h to ensure thorough and uniform mixing. The resulting precursor solution was then allowed to stand and age for 3 days to obtain BaBi4Ti4O. 15 Precursor solution.
[0047] S2. Dissolve 0.6068 g of lanthanum nitrate (99.9% purity), 0.1315 g of strontium acetate (98% purity), and 0.4951 g of manganese acetate tetrahydrate (99% purity) in a mixed solvent of 5 mL acetic acid, 1 mL deionized water, and 5 mL ethylene glycol methyl ether. Heat and stir at 90°C for 20 min to ensure complete dissolution. Then, cool to room temperature and stir continuously for 7 h to ensure thorough mixing. Allow the solution to stand and age for 12 h to obtain the conductive oxide electrode La. 0.7 Sr0.3 MnO3 precursor solution.
[0048] A (001) oriented LaAlO3 single crystal substrate was pretreated with plasma in air for 10 min at a power of 18 W and a working pressure of 60 Pa. A conductive oxide electrode, La, was then spin-coated onto the pretreated substrate. 0.7 Sr 0.3 The MnO3 precursor solution was spin-coated at 4000 r / min for 30 s. Then it was heated and dried at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter. Finally, it was annealed at 900 ℃ for 30 min to crystallize. The spin-coating, pyrolysis and annealing steps were repeated 4 times to obtain the bottom electrode layer.
[0049] S3. Spin-coat BaBi4Ti4O with an entropy value of 1.48 R onto the surface of the prepared bottom electrode layer. 15 The precursor solution was spin-coated at 6000 r / min for 20 s; then heated to 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally annealed at 675 ℃ for 30 min to crystallize. This spin-coating, pyrolysis, and annealing process was repeated 15 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95- 3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value of 0.3.
[0050] Example 5
[0051] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1, the same as step S1 in Example 2, yields BaBi4Ti4O 15 Precursor solution; S2. Dissolve 0.3468 g of lanthanum nitrate (99.9% purity) and 0.2011 g of nickel acetate tetrahydrate (99% purity) in 4 mL of ethylene glycol methyl ether solvent; heat and stir at 70 °C for 10 min to ensure complete dissolution, then transfer to room temperature and stir continuously for 5 h to ensure thorough mixing. Allow the solution to stand and age for 12 h to obtain the LaNiO3 precursor solution for the conductive oxide electrode. Then spin-coat the LaNiO3 precursor solution onto the pretreated substrate.
[0052] The (001) oriented LaAlO3 single crystal substrate was pretreated with plasma in air for 5 min at a power of 18 W and a working pressure of 60 Pa. The LaNiO3 precursor solution was then spin-coated onto the pretreated substrate at a spin speed of 5000 r / min for 20 s. Subsequently, the substrate was heated and dried at 150 °C for 2 min, then pyrolyzed at 450 °C for 5 min to remove organic matter, and finally annealed at 700 °C for 10 min to crystallize it. The spin-coating, pyrolysis, and annealing steps were repeated twice to obtain the bottom electrode layer.
[0053] S3. Spin-coat the precursor solution prepared in step S1 onto the surface of the bottom electrode layer at a spin speed of 6000 r / min for 20 s; then heat and dry at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally anneal at 625 ℃ for 30 min to crystallize it. Repeat the spin-coating, pyrolysis, and annealing steps 15 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95-3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value of 0.1.
[0054] Example 6
[0055] This embodiment provides an entropy-controlled textured BaBi4Ti4O 15 The specific steps for preparing the dielectric energy storage thin film are as follows: S1, the same as step S1 in Example 3, yields BaBi4Ti4O 15 Precursor solution; S2, the same as step S2 in Example 3, yields the conductive oxide electrode La. 0.7 Sr 0.3 MnO3 precursor solution.
[0056] The LaAlO3 single crystal substrate was pretreated with plasma in air for 15 min at a power of 18 W and a working pressure of 60 Pa. The aforementioned LaAlO3 was then spin-coated onto the pretreated substrate. 0.7 Sr 0.3 The MnO3 precursor solution was spin-coated at 5000 r / min for 30 s. It was then heated and dried at 150 °C for 2 min, followed by pyrolysis at 400 °C for 10 min to remove organic matter. Finally, it was annealed at 900 °C for 30 min to crystallize it. The spin-coating, pyrolysis and annealing steps were repeated 3 times to obtain the bottom electrode layer.
[0057] S3. Spin-coat the precursor solution prepared in step S1 onto the surface of the bottom electrode layer at a spin speed of 6000 r / min for 20 s; then heat and dry at 150 ℃ for 2 min, followed by pyrolysis at 400 ℃ for 10 min to remove organic matter, and finally anneal at 650 ℃ for 30 min to crystallize it. Repeat the spin-coating, pyrolysis, and annealing steps 16 times to obtain entropy-controlled textured BaBi4Ti4O. 15 The base dielectric energy storage thin film has the general chemical formula BaBi4Ti. 3.95-3x Hf x Zr x Sn x Mn 0.05 O 15 , where x represents the mole fraction, and x takes the value of 0.2.
[0058] Comparative Example 1
[0059] This comparative example provides a BaBi4Ti4O 15 The preparation method of the dielectric energy storage thin film is the same as in Example 1, except that the "single crystal substrate LaAlO3" in step S2 is replaced with a Pt / Ti / SiO2 / Si substrate, and finally BaBi4Ti4O is obtained. 15 Base film.
[0060] Structural characterization and performance testing: Figure 1 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 XRD pattern of the dielectric energy storage thin film. Figure 1 It can be seen that the products of Examples 1 to 4 are all pure phase BaBi4Ti4O 15 The structure is free of second-phase impurities.
[0061] Figure 2 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 The SEM image of the dielectric energy storage film shows that the prepared film has a dense microstructure, which is beneficial for obtaining high breakdown strength.
[0062] Figure 3 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 BaBi4Ti4O4 dielectric energy storage thin film and BaBi4Ti4O4 prepared in Comparative Example 1 15 The breakdown strength curve of the base film, and the entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4. 15 Polarization intensity curves of the dielectric energy storage film under an electric field of 2.5 MV / cm. (From...) Figure 3 It can be seen that the breakdown strength of the products in Examples 1 to 4 is more than three times that of the product in Comparative Example 1. In the range of 0 ≤ x ≤ 0.2, the breakdown strength of the samples gradually increases, reaching as high as 5.33 MV / cm when x = 0.2. In the range of 0 ≤ x ≤ 0.1, the polarization intensity of the samples under the isoelectric field increases synchronously, with the breakdown strength and polarization intensity of the product in Example 2 showing a significant improvement compared to the product in Example 1.
[0063] Figure 4 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 Hysteresis loop diagram of the dielectric energy storage thin film under electric fields ranging from -6 MV / cm to 6 MV / cm. Figure 4 It can be seen that the products of Examples 1-4 all exhibit slender hysteresis loops, while the product of Example 2 exhibits the largest polarization intensity value.
[0064] Figure 5 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 The graph shows the energy density and energy storage efficiency of the dielectric energy storage film as a function of electric field strength. Figure 5 It can be seen that the energy density of the product gradually increases with the increase of the electric field strength. Among them, the product of Example 2 achieved the highest energy density of 181.3 J / cm³ at an energy storage efficiency of 91.2%. 3 .
[0065] Figure 6 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 The graph shows the energy density and energy storage efficiency of the dielectric energy storage film as a function of frequency under an electric field of 2 MV / cm. Within the frequency range of 0.5–50 kHz, the energy density and energy storage efficiency of each product remain essentially constant, indicating their superior frequency stability.
[0066] Figure 7 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15 The graph shows the energy density and energy storage efficiency of the base dielectric energy storage film as a function of temperature under an electric field of 2 MV / cm. Within the temperature range of 173~573 K, the energy density and energy storage efficiency of the products of Example 2 and Example 3 show relatively small changes, indicating their superior temperature stability; when the temperature is higher than 450 K, the energy storage efficiency gradually decreases as the temperature continues to rise.
[0067] Figure 8 Entropy-controlled textured BaBi4Ti4O prepared in Examples 1-4 15The graph shows the variation of energy density and energy storage efficiency of the base dielectric energy storage film with the number of charge-discharge cycles under an electric field of 2 MV / cm. Example 1 product at 3 × 10⁻⁶... 5 The energy density and energy storage efficiency remain almost unchanged within the next cycle; the products of Examples 2 and 3 show that at 10 7 The energy density and energy storage efficiency remain almost unchanged within the next cycle; the product of Example 4 exhibits almost constant energy density and energy storage efficiency at 10 5 The energy density and energy storage efficiency remain almost unchanged during the next cycle, indicating that the fabricated thin film has excellent energy storage performance and cycle stability.
[0068] Figure 9 BaBi4Ti4O prepared for Comparative Example 1 15 Hysteresis loops of the base thin film under electric fields ranging from -1.5 MV / cm to 1.5 MV / cm. Figure 9 It can be known that BaBi4Ti4O 15 The breakdown strength of the base film is 1.24 MV / cm, and the maximum polarization intensity is 23.9 μC / cm. 2 The energy density is 14 J / cm³. 3 .
[0069] Those skilled in the art should understand that the above descriptions are merely several specific embodiments of the present invention, and not all embodiments. It should be noted that many modifications and improvements can be made by those skilled in the art, and all modifications or improvements not exceeding the scope of the claims should be considered within the protection scope of the present invention.
Claims
1. An entropy-controlled textured BaBi4Ti4O 15 A method for preparing a dielectric energy storage thin film, characterized in that, Includes the following steps: S1. Preparation of precursor solution: Weigh out barium, bismuth, titanium, hafnium, zirconium, tin, and manganese sources according to the molar ratio of metal elements 1:4.2:(3.95-3x):x:x:x:0.05, where 0≤x≤0.3; dissolve each metal source in a solvent to obtain a mixed solution, wherein the molar concentration of the main matrix metal barium (Ba) in the mixed solution is 0.1 mol / L; after heating and stirring, stirring at room temperature, and aging by static aging, obtain BaBi4Ti4O. 15 Precursor solution; S2. Plasma pretreatment is performed on the surface of the (001) oriented perovskite single crystal substrate to obtain an activated surface; A conductive oxide electrode precursor solution is coated on the activated surface, followed by low-temperature heating and drying, medium-temperature pyrolysis to remove organic components, and high-temperature annealing and crystallization treatment. The steps of coating to high-temperature annealing and crystallization treatment are repeated at least once to form a bottom electrode layer. S3. Coat the bottom electrode layer with the BaBi4Ti4O prepared in step S1. 15 The precursor solution was then subjected to a series of treatments, including low-temperature drying, medium-temperature pyrolysis to remove organic components, and high-temperature annealing crystallization, to produce BaBi4Ti4O. 15 The dielectric energy storage film is grown along the c-axis orientation and the process of high-temperature annealing and crystallization is repeated at least once to form an entropy-controlled textured BaBi4Ti4O. 15 Dielectric energy storage thin films; Steps S1 and S2 are not in any particular order.
2. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, In step S1, x is set to 0.1, and the barium source, bismuth source, titanium source, hafnium source, zirconium source, tin source and manganese source are weighed according to the molar ratio of metal elements 1:4.2:3.65:0.1:0.1:0.1:0.
05.
3. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, The barium source mentioned in step S1 is barium acetate, the bismuth source is bismuth acetate, the titanium source is tetrabutyl titanate, the hafnium source is hafnium acetylacetonate, the zirconium source is zirconium n-propoxide, the tin source is tin isooctanoate, the manganese source is manganese acetate tetrahydrate, and the solvent is propionic acid.
4. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, In step S1, the heating and stirring temperature is 70-90 ℃, and the stirring time is 10-20 min; the stirring time at room temperature is 6-7 h, and the aging time is 3-90 days.
5. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, In step S2, the conductive oxide electrode precursor solution is coated and heat-treated to form La. 0.7 Sr 0.3 MnO3 or LaNiO3 conductive oxide electrode films.
6. The entropy-controlled textured BaBi4Ti4O according to claim 1 or 5 15 A method for preparing a dielectric energy storage thin film, characterized in that, In step S2, the conductive oxide electrode precursor solution contains substances similar to the target compound La. 0.7 Sr 0.3 The corresponding molar ratio of MnO3 to lanthanum salt, strontium salt, manganese salt, and solvent, wherein the lanthanum salt is lanthanum nitrate with a concentration of 0.07-0.21 mol / L; the strontium salt is strontium acetate with a concentration of 0.03-0.09 mol / L; the manganese salt is manganese acetate tetrahydrate with a concentration of 0.1-0.3 mol / L; and the solvent is one or more of acetic acid, deionized water, and ethylene glycol methyl ether. Alternatively, the conductive oxide electrode precursor solution contains a lanthanum salt, a nickel salt, and a solvent in a molar ratio corresponding to the target LaNiO3, wherein the lanthanum salt is lanthanum nitrate with a concentration of 0.1-0.3 mol / L, the nickel salt is nickel acetate tetrahydrate with a concentration of 0.1-0.3 mol / L, and the solvent is ethylene glycol methyl ether.
7. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, In step S2, the perovskite single crystal substrate is a LaAlO3 single crystal substrate or a SrTiO3 single crystal substrate; plasma pretreatment is performed in an air atmosphere with a processing power of 7-18 W, a processing time of 5-15 min, and a working pressure of 30-60 Pa.
8. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, The coating method described in step S2 is spin coating, with a spin coating speed of 3000-5000 r / min and a time of 20-30 s; low-temperature heating drying at 120-200 ℃ for 1-2 min; medium-temperature pyrolysis at 350-450 ℃ for 5-20 min; and high-temperature annealing crystallization treatment at 700-900 ℃ for 20-30 min, repeated 2-8 times.
9. The entropy-controlled textured BaBi4Ti4O according to claim 1 15 A method for preparing a dielectric energy storage thin film, characterized in that, The coating method described in step S3 is spin coating, with a spin coating speed of 3000-6000 r / min and a time of 20-30 s; low-temperature heating drying at 120-200 ℃ for 1-2 min; medium-temperature pyrolysis at 350-450 ℃ for 5-20 min; and high-temperature annealing crystallization treatment at 600-750 ℃ for 20-30 min, repeated 10-18 times.
10. An entropy-controlled textured BaBi4Ti4O as described in any one of claims 1 to 9 15 Entropy-controlled textured BaBi4Ti4O prepared by a method for preparing dielectric energy storage thin films. 15 Dielectric energy storage film.
